A subfamily of a generalized petersen graph P(n,3) with constant metric dimension - Husnine S.M.; Kousar, Imrana (Utilitas Mathematica, 2010)
The cardinality of a basis of a connected graph G is called the metric dimension of G. In this paper, we present an infinite subfamily of generalized Petersen graph P(n, 3) with metric dimension 3.